2021
DOI: 10.3390/pr9101708
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Assisted Ultrasonic Extraction of Total Flavonoids from Acanthopanax senticosus and Their Enrichment and Antioxidant Properties

Abstract: Flavonoids are one of the important active ingredients from Acanthopanax senticosus, with a variety of biological functions, such as antioxidant and antibacterial properties. The aim of this work was to investigate enzyme-assisted ultrasonic extraction of A. senticosus flavonoids and their enrichment and antioxidant properties. We found that the optimal extraction process after Box–Behnken response surface optimization had the following parameters: a 3:2 ratio of cellulase to pectinase, enzyme mixture amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Examined extracts at a concentration of 0.80 mg/mL, expressed DPPH reduction in the range of 14.7 to 26.2%, with E. gracilistylus as the most active species. In turn, Liu et al [ 32 ] have investigated the potential of chemical compounds possessed by E. senticosus , such as flavonoids, and phenolic acids, and correlated it with its potential to reduce DPPH and ABTS, proving that high concentrations of those components are positively correlated with high antioxidant activity. Those findings stand in line with our current and previous reports [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Examined extracts at a concentration of 0.80 mg/mL, expressed DPPH reduction in the range of 14.7 to 26.2%, with E. gracilistylus as the most active species. In turn, Liu et al [ 32 ] have investigated the potential of chemical compounds possessed by E. senticosus , such as flavonoids, and phenolic acids, and correlated it with its potential to reduce DPPH and ABTS, proving that high concentrations of those components are positively correlated with high antioxidant activity. Those findings stand in line with our current and previous reports [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The highest total saponin (11.45%) content was obtained when 5 g of sample was extracted with 75 mL of 73% ethanol at 400 W and 61 °C for 34 min. Liu et al [ 220 ] studied the EAE of saponins from powdered Acanthopanax senticosus . The extraction was carried out at different enzyme concentrations (1000, 5000, and 9000 U/g), time durations (45, 55, and 65 min), temperatures (40, 50, and 60°C), and solvent pH values (5.4, 6, and 6.6).…”
Section: Suitability Of the Methods For The Extraction Of Various Bio...mentioning
confidence: 99%
“…Modern pharmacological experiments have demonstrated that A. senticosus possessed antistress, antioxidant, antiapoptotic, and hepatoprotective activities [11]. Previous works showed that the n-butanol fraction of A. senticosus extracts (NASE) has higher antioxidant activity in vitro [12]. As reported in the literature, nbutanol fractions of AS signifcantly prolong the swimming time of mice to exhaustion [13].…”
Section: Introductionmentioning
confidence: 93%
“…Previous works showed that the n-butanol fraction of A . senticosus extracts (NASE) has higher antioxidant activity in vitro [ 12 ]. As reported in the literature, n-butanol fractions of AS significantly prolong the swimming time of mice to exhaustion [ 13 ].…”
Section: Introductionmentioning
confidence: 99%